Neuroanatomical Alterations in Patients With Tinnitus Before and After Sound Therapy: A Voxel-Based Morphometry Study - Wei, Xuan; Lv, Han; Wang, Zhaodi; Liu, Chunli; Ren, Pengling; Zhang, Peng; Chen, Qian; Liu, Yawen; Zhao, Pengfei; Gong, Shusheng; Yang, Zhenghan; Wang, Zhenchang (Frontiers in Neuroscience, 2020)
According to previous studies, many neuroanatomical alterations have been detected in patients with tinnitus. However, only limited studies reported the morphological changes after sound therapy with relative short time. To explore the brain anatomical alterations in patients with idiopathic tinnitus using voxel-based morphometry (VBM) analysis before and after effective 12 weeks sound therapy. The protocol was registered on ClinicalTrials.gov, ID: NCT02774122. We collected data from 27 idiopathic tinnitus patients before and after 12 weeks of sound therapy by using adjusted narrow band sound and from 27 matched healthy control (HC) individuals in this study. 3.0T MRI system and high-resolution 3D structural images were acquired with a 3D-BRAVO pulse sequence. Structural image data preprocessing was performed using the VBM8 toolbox. The Tinnitus Handicap Inventory (THI) score was acquired in the tinnitus group to assess the severity of tinnitus and tinnitus-related distress. Two sample t-tests, paired-samples t-tests, and Pearson’s correlation analysis were used in the statistical analysis. We found significantly decreased gray matter (GM) volume in the left and right thalami and cochlear nucleus among the tinnitus patients before sound therapy (baseline) compared to the HC group. But we did not find significant difference of brain regions between the 12-week treatment and HC groups. According to the results of paired-samples t-tests, the 12-week sound therapy group demonstrated significant greater brain volume compared with the baseline group among these brain regions. Decreased THI score and changed GM volume were not correlated. This is a meaningful study to observe the characteristics of neuroanatomical changes in patients with idiopathic tinnitus before and after sound treatment. The study characterized the effect of sound therapy on brain volume. Sound therapy had a normalizing effect on the bilateral thalami and cochlear nucleus.